Pengaruh tarif bea masuk, profil importir, frekuensi impor, fasilitas kepabeanan, dan nilai pabean pada tax evasion di bidang kepabeanan - Sumadi, Tia Rizkya Dilbar; Nurkhamid, Muh (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Currently, the Directorate General of Customs and Excise (DGCE) is facing challenges in balancing the service and supervisory functions through Post-Clearance Audit (PCA). Through quantitative studies, this research aims to analyze the effect of the criteria for determining the object of the audit: customs duty tariff, importer profile, import frequency, customs facilities and customs value on tax evasion in the customs sector. This study uses secondary data obtained from internal data of DGCE with a sample of 400 companies selected. This research uses multiple regression analysis method with the results showed that the variable import frequency, customs facilities, and customs value individually had a positive and significant effect on tax evasion on customs, while the variable import duty rates and importer profile individually had no significant effect. Simultaneously, the variable customs duty tariff, importer profile, import frequency, customs facilities and customs value have a positive and significant effect on tax evasion in the customs sector. This research is expected to be an input reference for the Directorate Audit of Customs and Excise of DGCE in an effort to improve customs audit performance by focusing on audits on companies that have large tax evasion potential.